Reforma al inciso final del artículo 435 del código orgánico integral penal a fin de garantizar el derecho a la defensa del procesado - Dávila Verduga, Ronnie Valeria (2017)
This research work whose theme is "REFORM INCISO END OF ARTICLE 435 OF THE CODE ORGANIC INTEGRAL CRIMINAL TO ENSURE THE RIGHT TO DEFENSE OF PROCESSED" so that the objective of this research is aimed at establishing a reform final paragraph in which the summons by the press as in the civil or administrative procedure enabling this way to the summons of the defendant and not the right to self-defense is violated, making known the same extract of the complaint stated. The constitutional right to legal certainty is a universal principle by which the courts and administrative bodies responsible for administering justice are subject to ensure that the proper application of each and every one of the rights guaranteed in any procedure and guarantees of the parties this within the framework of clear and correct rules that strengthen the entire universe of constitutional rule of law, and this is where the citation is set to the plaintiff person to know the reason for the complaint submitted to it. As is common knowledge the situation is the means by which it is made known for the first time a court action against a person whether they have the quality of defendant in civil and administrative or denounced in criminal matters is which concerns us, in this area the prosecution provided for in the fourth chapter of title Two Organic Code Integra Criminal establishes each and every one of the requirements for their origin and which refers to the citation in the final paragraph of Article 435 does not determine that when the domicile of the defendant is unknown it quoted by the press and instead establish that it does dare the Public defender, which in my opinion is a clear violation of the constitutional right or defense legal certainty because this way the defendant would never come to know about the prosecution imposed against him. The citation for the press is a means by which both civil and criminal laws are planned to be effective in any process the right to defend one part in a Litis, so that the Constitutional status of rights is rooted in these principles which strengthen legal certainty and respect for the procedural rules which are garantistas and be required to be met, which is why I believe that the summons by the press should be included in this related rule that is followed not violating rights of the accused in criminal proceedings, in Which there is private prosecution This thesis Legal Research is structured as follows: First a Conceptual Framework, comprising concepts and definitions, as we have the right to defense, as well as other items that will give greater prominence to the proposed theme; doctrinaire framework, covering the doctrines of writers and scholars on the conceptualization of the topic. and a legal framework, which includes the analysis of the Constitution of the Republic of Ecuador, the Organic Code Integral Penal, and then we have a comparative legislation because it helped me to make an analysis of matter from other countries and to extract the most positive. Secondly the research work includes a field study in which surveys and interviews are developed connoisseurs of law in helping me determine or contrast the objectives and hypotheses raised. Third after the analysis of field research we proceeded to the conclusions and recommendations and finally to a legal proposal necessary for the solution of the problem.